Mendukung Diversifikasi Usaha Kelompok Pengolahan Perikanan Usaha Mikro Kabupaten Maluku Tenggara - Teniwut, Roberto Mario Kabi; Ngangun, Tati Atia; Pentury, Frischilla; Hamid, Syahibul Kahfi; Rahantoknam, Meyske Angel; Hasyim, Cawalinya Livsanthi; Teniwut, Wellem Anselmus (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Following the Covid-19 outbreak, the number of fisheries processing organisations in Southeast Maluku Regency declined significantly. The Sibit group in Loon Village is one of the groups that is still operating and is striving to expand its operation through business diversification. The goal of this service activity is to assist the Sibit group with expanding their business by acquiring product label legality, product quality testing, yesterday product design, and general management competence enhancement. Counseling, training, and direct help to partners in fisheries processing business groups are employed to attain this specific purpose. The business group supported and responded positively to this community service initiative. There is a fundamental concept of management and business management, as well as the growth of expansion through the diversity of processed products generated.